The Association Between Neutrophil To Lymphocyte Ratio and Disease Activity In Rheumatoid Arthritis - عمار, رود; الدو , كاسر (Latakia University Journal -Medical Sciences Series, 2022)
Background: Neutrophil-Lymphocyte Ratio (NLR) is reported to be increased in various inflammatory diseases, but its significance in Rheumatoid Arthritis remains unclear. Inflammation is the key determinant and primary underlying mechanism leading to disability and increased mortality in patients with rheumatoid arthritis (RA). Therefore, assessment of inflammation in RA with reliable markers is crucial to predict long-term outcome of a particular patient. Aim: The aim was to study the association between Neutrophil to Lymphocyte Ratio and disease activity in Rheumatoid Arthritis, and to compare between active cases and those in remission. Also the association between this ratio and other factors such as: HGB, PLT, ESR, CRP, RF and ACPA. Materials & Methods: A cross-sectional study was performed that included 71 patients diagnosed with Rheumatoid Arthritis according to the 2010 ACR/EULAR criteria, who were admitted to the Department or the clinic of Rheumatology Diseases at Tishreen University Hospital in Lattakia during the period between November 2020 and November 2021 AD, and who fulfilled the inclusion criteria in the research. The following laboratory analyzes were performed: complete blood count (CBC), CRP, ESR, RF, ACPA and we calculated the DAS-28(CRP) value and NLR to these patients. The patients were divided into 4 study groups according to the value of DAS-28 as follows: (remission of 7 patients, mild efficacy of 9 patients, moderate efficacy of 36 patients, and severe effectiveness of 19 patients). The research sample also included 71 healthy age and gender matched individuals as a control group, where the same laboratory analyzes were performed and the results were compared with them. Also, the curves (ROC Curve) were used to find out the best cut-off point of the neutrophils to lymphocytes ratio that predict the effectiveness of the disease. Results: The NLR was statistically significantly higher in patients with rheumatoid arthritis compared with the control group. There was a statistically significant positive correlation between NLR and DAS-28 in patients with rheumatoid arthritis. we didn’t find any statistically significant association between NLR and the following parameters: ESR, CRP, RF, ACPA and WBC. The most sensitive inflammatory indicator that predict the increasing in disease activity was ESR, followed by CRP and then NLR. The best cut-off point for the neutrophils to lymphocytes ratio was set at 2.53, with a sensitivity of 71.4% and a specificity of 62.4%. Conclusion: NLR is a cheap and readily available inflammatory indicator that is well correlated with other inflammatory indicators and disease activity indices in RA. Hence, NLR could be a useful single tool for the assessment of disease activity in RA.